O enfrentamento dos portadores de insuficiência renal crônica: uma abordagem sobre a perspectiva e adaptação diante de um novo estilo de vida - PINHEIRO, Márcia Cristina Abreu (2019)
This research has as study object the confrontation of the carriers of chronic renal insufficience ahead of its new style of life. To guide this research, an only question is distinguished: How if of the o confrontation of individuals, carriers of chronic renal insufficience ahead of the change in its style of life? To answer to these questionings the following objective was elaborated: To know to understand the form of confrontation of the chronic renais patients in relation to its new style of life. The study it was of the descriptive, transversal type with qualitative boarding, using itself of mechanisms of psychological adaptations. For attainment of the information the half-structuralized interview was used, applied the fifteen carriers of IRC with for the little six months of diagnosis confirmed and submitted to hemodiálise, users of the Unit of Therapy Substitute of the Public foundation State Hospital of Clinics Caspar Vianna (FHCGV) of the city of Belém/PA. For analysis it was opted to the technique of thematic analysis, having as resulted the appearance of four thematic units: Religiosidade and Espiritualidade: the base of the confrontation, the importance of the familiar support in the treatment of the IRC, the work: a challenge ahead of the limitations imposed for the renal illness and Feelings and perspectives of life of the patient in relation renal illness. The results had evidenced how the interviewed ones react before the new reality, as well as the psychological strategies used by the same ones to adaptarem its new condition.